Scoring Systems for Postthrombotic Syndrome - Wik, Hilde Skuterud; Ghanima, Waleed; Sandset, Per Morten; Kahn, Susan R. (Seminars in Thrombosis and Hemostasis, 2017)
Postthrombotic syndrome (PTS) is the most common long-term complication after deep vein thrombosis (DVT) and is associated with reduced quality of life. There is no single objective test to diagnose the presence of PTS and it is usually diagnosed on the basis of typical symptoms and signs in a limb previously affected by DVT. Scoring systems for PTS are primarily developed as research tools, but could possibly also be useful in the clinical setting. A main advantage of a good scoring system is standardization of the diagnostic process. An optimal scoring system should be both sensitive and specific for PTS, but this has been difficult to achieve because the symptoms and signs of PTS can be similar to other conditions leading to complaints in the lower limb. In an effort to standardize the definition of PTS, in 2009, the International Society on Thrombosis and Haemostasis Subcommittee on Control of Anticoagulation reviewed available scales and recommended use of the Villalta scale as the most appropriate measure to diagnose and grade the severity of PTS. The aim of this article is to review the existing scoring systems for PTS and to present our view on the advantages and disadvantages of these diagnostic tools.
Keywords: postthrombotic syndrome; diagnosis; scoring systems